(untitled) (Global Business Management Review (GBMR), 2022)
In this paper, we examine the relationship between board monitoring mechanism, continuous training and financial reporting quality in Malaysian context. The paper employed a sample of top 100 Malaysia firms identified by the Malaysia Shareholder Watchdog Group (MSWG) between the periods 2010-2011. Feasible GLS (FGLS) regression estimation method was used to test the relationship between the dependent variable of interest. The regression result reveals that while the proportion of grey directors in boardroom positively and significantly relates with both accrual and real earnings management, the proportion of independent directors was negative, but not significant. Board continuous training and outsourcing of internal audit function is however negatively and significantly affects accrual and real earnings management. The study’s findings have implication for future regulatory initiative, as our result suggests that board mechanisms, specifically, board composition are not effective in improving the quality of reported figures. This study extend previous studies by testing whether board experience measured by the number of continuous education training program- trainings relating to corporate governance and financial reporting attended by board members improve the quality of financial reporting.